Anxiety Predicts Poor Prognosis in Patients With Hypertrophic Cardiomyopathy - He, Chao-Jie; Zhai, Chang-Lin; Huang, Shao-Dai; Fan, Hong-Yan; Qian, Ye-Zhou; Zhu, Chun-Yan; Hu, Hui-Lin (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypertrophic cardiomyopathy (HCM) is the prevalent inherited cardiomyopathy and a major contributor to sudden death and heart failure in young adults. Although depression has been associated with poor prognosis in patients with cardiovascular disease, the relationship between anxiety and HCM clinical outcomes has not been addressed. We aimed to determine the prevalence of anxiety symptoms in patients with HCM and the association between anxiety and adverse prognosis in this population. Methods: A total of 793 patients with HCM were prospectively enrolled and followed up for a mean of 4.1 years from March 2014 to January 2018. The primary endpoint was sudden cardiac death (SCD) events, and the secondary endpoint was HCM-related heart failure events. Anxiety symptoms were assessed using the Hospital Anxiety and Depression Scale (HADS) during outpatient visits or hospital stays. Results: Elevated scores on the HADS anxiety subscale (HADS-A ≥ 8) were defined as clinically significant anxiety. SCD and HCM-related heart failure events occurred in 76 and 149 patients, respectively, during the follow-up period. Kaplan–Meier survival curves demonstrated the significant association of anxiety with SCD events (log-rank P = 0.012) and HCM-related heart failure events (log-rank P = 0.001). Multivariable Cox regression analysis showed anxiety as a predictor of SCD events and HCM-related heart failure events (adjusted hazard ratio [HR] = 1.42, 95% confidence interval [CI] = 1.12–2.04, P = 0.03; adjusted HR = 2.9,2 95% CI = 1.73–4.03, P < 0.001), independent of conventional risk factors and depression. Besides, patients with comorbid anxiety and depression showed a fourfold higher risk of heart failure events and 3.5-fold higher risk of SCD versus those with neither (adjusted HR = 4.08, 95% CI = 2.76–5.91, P < 0.001; adjusted HR = 3.52, 95% CI = 2.24–4.67, P < 0.001, respectively). Conclusions: Anxiety was prevalent among Chinese patients with HCM, and it was independently associated with a higher risk of SCD and HCM-related heart failure events, particularly when comorbid with depression. Psychological assessment and intervention should be considered to alleviate anxiety symptoms in this population.